The Good Neighbors. Book one, Kin - Black, Holly; Naifeh, Ted (New York : Graphix, 2008)
Sixteen-year-old Rue Silver, whose mother disappeared weeks ago, believes she is going crazy until she learns that the strange things she has been seeing are real, and that she is one of the faerie creatures, or Good Neighbors, that mortals cannot see.
Booklist.
Horn Book.
School Library Journal.
5.4
5-8
Keywords: Fairies -- Comic books, strips, etc. -- Juvenile fiction; Magic -- Comic books, strips, etc. -- Juvenile fiction; Supernatural -- Comic books, strips, etc. -- Juvenile fiction; Cartoons and comics; Fairies -- Fiction; Fantasy; Magic -- Fiction; Supernatural -- Fiction; Comic books, strips, etc; Fairies -- Comic books, strips, etc. -- Fiction; Fantasy graphic novels; Graphic novels; Magic -- Comic books, strips, etc. -- Fiction; Supernatural -- Comic books, strips, etc. -- Fiction; Fantasy comic books, strips, etc; Graphic novels